(untitled) (Perspectivas em Ciência da Informação, 2009)
For these last twenty years, the teachers-information officers of the French educational system follow during their professionalization, two years of teaching centred in particular on the sciences of the information and the communication (SIC). During this communication, we shall at first try to show how builds itself gradually this professional and scientific culture of the information, for secondly, observe the forms of mediation developed on the ground by the actors, during their first professional activities in school. Four types of mediation seem to prevail at the observed teacher’s-information officer’s.